TINDAKAN DEBT COLLECTOR DALAM MENAGIH UTANG PERSPEKTIF HUKUM PIDANA ISLAM (ANALISIS PUTUSAN PENGADILAN NEGERI SAWAHLUNTO NOMOR 73 PID.B/2018/PN SWL) - Rahmadani Rahmadani; Laila Afni Rambe (IAIN Ambon, 2022)
This research is motivated by the different views of Islamic criminal law on the decision of the Sawahlunto District Court number 73 / Pid.B / 2018 / PN SWL. The objectives to be achieved in this study are to find out the description of the debt collection case in the Sawahlunto District Court decision number 73 / Pid.B / 2018 / PN SWL. Knowing the judge's consideration in the decision of the Sawahlunto District Court number 73 / Pid.B / 2018 / PN SWL. Analyzing the decision of the Sawahlunto District Court number 73 / Pid.B / 2018 / PN SWL and comparing it with books related to the discussion. The method used in this research is normative research. Based on data obtained from the results of research data contained in the decision of the Sawahlunto District Court number 73 / Pid.B / 2018 / PN SWL, the following conclusions are obtained, namely: first, the description of the case in the decision when withdrawing goods using the Vehicle Handover Certificate (BASTK) ) which is in accordance with the original and in the debt collector's claim admitted as a member of the police who was not proven at the trial. Second, the judge's consideration in the decision of the Sawahlunto District Court number 73 / Pid.B / 2018 / PN SWL was the violation of Article 378 of the Criminal Code. Third, the view of Islamic criminal law on the decision of the Sawahlunto District Court number 73 / Pid.B / 2018 / PN SWL debt collector cannot be said to have committed a criminal act of fraud. Because cheating in Islamic criminal law is using false words, while when withdrawing goods, debt collectors do not use lying words. And what is the obligation to pay this debt is the debtor, while in the decision of the Sawahlunto District Court number 73 / Pid.B / 2018 / PN SWL the prosecutor is the debtor who should settle all of his debts.